Strongly Essentially Quasi-Dedekind Modules - Hadi, I. M.A.; Ghawi, T.Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Let R be a commutative ring with unity. In this paper we introduce and study the concept of strongly essentially quasi-Dedekind module as a generalization of essentially quasiDedekind module. A unitary R-module M is called a strongly essentially quasi-Dedekind module if ( , ) 0 ï€½Hom M N M for all semiessential submodules N of M. Where a submodule N  of  an R-module  M  is called semiessential if , 0 ï‚¹ïƒ‡ pN for all nonzero prime submodules  P of  M .